Onset of occupational hand eczema among healthcare workers during the SARS‐CoV‐2 pandemic: Comparing a single surgical site with a COVID‐19 intensive care unit. (16th June 2020) - Guertler, Anne; Moellhoff, Nicholas; Schenck, Thilo L.; Hagen, Christine S.; Kendziora, Benjamin; Giunta, Riccardo E.; French, Lars E.; Reinholz, Markus
Abstract: Background: As a result of the COVID‐19 outbreak, hygiene regulations have been revised and hand sanitation has been intensified. Objective: To investigate the onset of hand eczema during the COVID‐19 pandemic in healthcare workers (HCWs) directly involved in intensive care of COVID‐19 patients and HCWs without direct contact with COVID‐19 patients. Hereby, we aim at increasing awareness about occupational hand eczema and preventive measures that can be adopted. Method: A survey was distributed amongst 114 HCWs at a single surgical centre and at a COVID‐19 intensive care unit of the university hospital Ludwig Maximilian University Munich, Germany. Participants were questioned about the daily frequency of hand hygiene prior to and during the pandemic. Participants self‐reported the onset of hand eczema and associated symptoms. Results: Our study revealed a significant increase in hand washing, disinfection, and use of hand cream across all participants ( P ‐value <.001), regardless of having direct contact with COVID‐19 patients. A high prevalence of symptoms associated with acute hand dermatitis of 90.4% was found across all HCWs, whereas hand eczema itself was underreported (14.9%). Conclusion: The increase in hand sanitation during the COVID‐19 pandemic impairs the skin of the hands across all HCWs, independent of direct intensive care of affected patients.